Pengaruh Senam DM Terhadap Kadar Gula Darah Sewaktu Pada Penderita DM Tipe II Di Puskesmas Tuminting - Sarwan Sarwan; Zainar Kasim (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Diabetes Mellitus (DM) is a disorder in the processing of carbohydrates in the body, caused by a lack of hormone of insulin so that the carbohydrate cannot be used by the cell to be converted into energy. The purpose of this research was to find out the effect of the DM Gymnastic on fasting Blood Sugar Level in patients with type II DM at the Tuminting Public Health Center. The Research was conducted by using an analytic descriptive method that is cross sectional in characteristic. The sample was 17 respondents taken by using an Purposive Sampling. Instruments used in taking sample were pretest-posttest Blood Sugar Observating sheets and the SOP of DM Gymnasic. Data analysis used a statistic test of paired t-test. The result showed that from the paired t-test, it was obtained P=0,002. The average value of Blood Sugar level before performing DM Gymnastic was 145,41. Then, the average value after doing the DM Gymnastic was 129,71. The conclusion of this research that there is an effect of the DM Gymnastic on fasting Bloood Sugar Level in patients with type II DM at the Tuminting Public Health Centre.